FORMATION OF AN INSTITUTE OF INDUSTRY INNOVATION SYSTEMS BASED ON THE SYMBIOSIS OF SCIENCE, STATE AND AGRIBUSINESS - Ivan SANDU; Vasily NECHAEV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Increasing agricultural production volumes to ensure food security of the country is inextricably linked with increasing the efficiency of integration between the state, science and agribusiness. The aim of the work is to improve the theoretical provisions for the formation of the Institute of Industry Innovation Systems and the tools for assessing the effectiveness of the Federal Scientific and Technical Program for the Development of Agriculture for 2017-2030. Methodological aspects of building the Institute of Industry Innovation Systems based on the transfer of positive foreign experience have been developed. Directions for adapting the AIS, ACIS, NARS systems to regional and industry conditions of the agricultural sector of the Russian economy have been proposed. The dynamics of production indicators for individual types of agricultural activity within the framework of the state program has been studied. Based on the results of the analysis and assessment of the effectiveness of the implementation of the FSTP subprograms, areas for growth in the production of sugar beets, potatoes, beef cattle and forage production have been identified.In order to maintain positive trends and increase agricultural production volumes, a systemic and functional approach is proposed to improve the efficiency of interaction between the state, science, and agribusiness based on the harmonization of their functions and interests. The practical significance of new models and mechanisms for the formation of the Institute of Industry Innovation Systems consists in increasing the growth of agricultural production through a balanced interaction between science, the state, and agribusiness for the neo-industrial development of the agricultural sector of the Russian economy.